PROGRAM PENINGKATAN SRADA DAN BAKTI UMAT HINDU DENGAN MEDIA SIMAKRAMA DI PURA GOA LAWAH KOTA MATARAM NUSA TENGGARA BARAT - Dewi, Ni Luh Sinar Ayu Ratna; Arjana, Ida Bagus Made; Sudarmaa, I Made; Pranama, Ida Bagus Beni Surya Adi; Sueca, I Nyoman; Yadnya, Made Sutha (Jurnal Pepadu, 2024)
The concept of Nyegara-Gunung means that humans give their minds and minds which must always be cleaned, cleaned or wound from top to bottom, one of which is held at the Goa Lawah Temple, Mataram City. The provision of telescopes and chairs can provide a medium to accommodate people's aspirations in a sitting position as well as comfort from the hot sun to communicate regarding knowledge of Tattwa, Ethics and Events (Upakara) the embodiment of simakrama in the Goa Lawah Temple area. At Goa Lawah Temple, which was initially hot in the heat of the sun, can now be cooler because there is a telescope and for elderly people who find it difficult to bend their knees, they can now use chairs to straighten their legs without crossing their legs. comes to every head of the family.